Anastomotic Troubleshooting - Sell, Naomi M.; Francone, Todd D. (Clinics in Colon and Rectal Surgery, 2021)
Anastomotic leak remains a critical and feared complication in colorectal surgery. The development of a leak can be catastrophic for a patient, resulting in overall increased morbidity and mortality. To help mitigate this risk, there are several ways to assess and potentially validate the integrity of a new anastomosis to give the patient the best chance of avoiding this postoperative complication. A majority of anastomoses will appear intact with no obvious sign of anastomotic dehiscence on gross examination. However, each anastomosis should be interrogated before the conclusion of an operation. The most common method to assess for an anastomotic leak is the air leak test (ALT). The ALT is a safe intraoperative method utilized to test the integrity of left-sided colon and rectal anastomoses and most importantly allows the ability to repair a failed test before concluding the operation. Additional troubleshooting is sometimes needed due to technical difficulties with the circular stapler. Problems, such as incomplete doughnuts and stapler misfiring, do occur and each surgeon should be prepared to address them.
Keywords: anastomotic leak; air leak test; colorectal surgery